STUDI KELAIKAN PEMANFAATAN PLASTIK TYPE 5 DAN TIPE 6 SEBAGAI MATERIAL LAMBUNG KAPAL - Asrun Sobirin Nasution (2021)
Plastic waste is a problem that has emerged in the world, the government has made many efforts to reduce the amount of plastic waste, such as reducing the use of single-use plastics in everyday life. Type 5 and type 6 plastic waste is quite widely used, especially for food and beverage packaging. To reduce the amount of plastic waste type 5 and type 6, a composite material was made using the Hand lay-up method for alternative shipbuilding materials. Tensile and bending testers were also carried out for the composite materials used. The manufacture of this composite material uses Yukalac 157 resin as a binder polymer from plastic filaments, so that it will add strength to the plastic composite. Based on the test results, it was found that the tensile strength of type 5 plastic composites got the greatest stress value, namely 3.62 Mpa with the 3rd arrangement composition while for type 6 got the greatest stress value, namely 12.17 Mpa with the 3rd arrangement composition. The tensile strength also obtained the strength value of type 5 plastic composites, the greatest bending stress value was 11.47 Mpa with the 3rd arrangement composition, while for type 6 the greatest stress value was 24.93 Mpa with the 3rd arrangement composition. In this study, the tensile and flexural strength of the platinum composite types 5 and 6 have not exceeded the tensile and flexural strength of fiberglass of 100 Mpa for the tensile test and 150 Mpa for the bending test.